Altman Z-Score Vs Zmijewski X-Score Dalam Memprediksi Kebangkrutan Perusahaan (Studi Kasus PT Tiga Pilar Sejahtera (AISA) Tahun 2015-2017) - Fanita Dahni (Universitas Diponegoro, 2019)
Many kind of methods for predicting bankruptcy have their respective characteristics and each methods have different characteristics. The results of the calculation of each method can give the same or even different results. In this study intended to predict whether the PT Tiga Pilar Sejahtera Food, Tbk (AISA) the results of the Altman Z-Scores and Zmijewski calculations have the same results, both of which can predict the company bankrupt, not bankrupt, or both models produce different results. In conducting this research, the author uses descriptive study methods and case studies. The data used are secondary data obtained from the company's official website. The research proves that: (1) Altman Z-Score calculation predicts that AISA indicates bankruptcy in the 2015-2017 period; (2) Zmijewski X-Score calculation predicts that AISA is in safe condition; (3) There are differences in the calculation results between Altman Z-Score and Zmijewski X-Score; (4) Differences can be triggered by differences in the ratio components used in the calculation of each method. This research is only a description of the company's condition which is not 100% correct. The results of the calculation methods are used as an evaluation in the future so that the company can improve its performance. This research can also be used as an illustration to make investment decisions for investors.